2021
DOI: 10.1111/nep.13939
|View full text |Cite
|
Sign up to set email alerts
|

Reducingnon‐melanomaskin cancer risk in renal transplant recipients

Abstract: With an increasing number of renal transplant recipients (RTRs) and improving patient survival, a higher incidence of non-melanoma skin cancer (NMSC) has been observed. NMSC in RTRs are often more numerous and biologically more aggressive than the general population, thus contributing towards an increase in morbidity and to a lesser degree, mortality. The resultant cumulative health and financial burden is a recognized concern. Proposed strategies in mitigating risks of developing NMSC and early therapeutic op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 197 publications
(187 reference statements)
0
18
0
Order By: Relevance
“…One small trial revealed that improvement in sun‐protective behaviours after education reduced the development of new skin lesions related to sun damage and new invasive SCCs 27 . Frequent assessment of sun protection compliance, establishment of an integrated skin cancer surveillance programme and timely detection of skin cancer are essential to reduce the risks of skin cancers among solid organ transplant recipients 6,23,25,26 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One small trial revealed that improvement in sun‐protective behaviours after education reduced the development of new skin lesions related to sun damage and new invasive SCCs 27 . Frequent assessment of sun protection compliance, establishment of an integrated skin cancer surveillance programme and timely detection of skin cancer are essential to reduce the risks of skin cancers among solid organ transplant recipients 6,23,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…2 RTRs are at increased risk of skin cancers especially nonmelanoma skin carcinoma (NMSC) (predominately basal cell carcinoma [BCC] and squamous cell carcinoma [SCC]) due to advanced age at transplant, use of immunosuppressants, smoking, male sex and oncogenic viruses. [3][4][5][6] A recent study in Central Queensland demonstrated that the lifetime risk for NMSC increased significantly from 18% pretransplant to 46% posttransplantation among RTRs with first kidney graft. 7 This increased risk is particularly relevant for Queensland, Australia, where the geographic proximity to the equator heightens ultraviolent (UV) exposure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basal cell carcinoma in Caucasians accounts for 75 to 80% of skin cancer cases, followed by squamous cell carcinoma (SCC) with 20 to 25% of cases and very small percentages for melanoma and other even rarer neoplasms (Thet et al, 2021). Approximately 90% of basal cell carcinomas are most frequently located in sun-exposed areas, that is, the face, ears, scalp, and arms (Karlsson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%